2021
DOI: 10.3390/nu13082734
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Nutrient Adequacy in China’s Food Supply from 1965 to 2018

Abstract: Nutritional intake has important impacts on human health. A sufficient supply of nutrients is required to ensure high-level nutrition in a population. Assessment of nutrient supply adequacy can help to develop evidence-based policies and thereby promote public health. This study estimates the supply adequacy of nutrients in China’s food system from 1965 to 2018 at the national level, aiming to reveal whether the supply of nutrients meets the demand. The results show that the nutrient supply in China’s food sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This is the first epidemiological study of calcium intake levels, urinary PGE-M levels, and risk of colorectal adenoma in western China. Currently, calcium is still one of the most deficient nutrients among Chinese residents, and this situation may be even more serious in western China (35). We hypothesize that high levels of PGE 2 may be determined by a combination of calcium deficiency and individual genetic susceptibility.…”
Section: Discussionmentioning
confidence: 92%
“…This is the first epidemiological study of calcium intake levels, urinary PGE-M levels, and risk of colorectal adenoma in western China. Currently, calcium is still one of the most deficient nutrients among Chinese residents, and this situation may be even more serious in western China (35). We hypothesize that high levels of PGE 2 may be determined by a combination of calcium deficiency and individual genetic susceptibility.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that the accessibility and availability of food increased, while our study did not include these variables. Liu et al found that the food supply had sharply increased and the deficiency in nutrient supply had been greatly mitigated in the past five decades in China [ 20 ]. Another study documented that, due to the rapidly growing e-commerce market, food accessibility and availability in China have improved [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cereals and legumes are two most important crops for national food security as they are the major sources for carbohydrate and plant-based protein in food system [40]. In addition, these two categories of crops, especially maize and soybean, are also the major feedstocks for chicken and pig.…”
Section: Discussionmentioning
confidence: 99%